The effect of stock return and ownership structure on investment risk in manufacturing companies listed on the Indonesian Stock Exchange (IDX) 2011 - 2013 - Anggraeni Meliana; Nurul Hasanah Uswati Dewi (Universitas Hayam Wuruk Perbanas, 2015)
This research aims to examine the effect of stock returns and ownership structure on the investment risk. The variables of this study are dependent variable, consisting of investment risk, and independent variable, consisting of stock return and ownership structure. The ownership structure in this study is measured using managerial own-ership and institutional ownership. The study sample consists of 101 manufacturing companies listed on the Indonesian Stock Exchange (IDX) 2011-2013. The result indicates that stock return has a positive effect on investment risk. If the investors expect the higher return rate, they must have the courage to bear the higher risk. The ownership structure does not have a negative effect on investment risk. It is because the ownership structure of a company is not included among the factors that affect the size of the investment risk that is likely to be experienced by investors. The implication of this study is that investors pay less attention to the ownership of the company to be invested. Therefore, the investors are expected to be more aware of the importance of ownership and corporate governance. Thus, it can reduce the failure experienced by investors in investing.